Pesticide pollution in argentine drinking water: A call to ensure safe access - Aparicio, Virginia Carolina; De Geronimo, Eduardo (Elsevier, 2024)
The application of pesticides in Argentina has been on the rise since 2000. However, the monitoring of pesticides in drinking water lacks regular updates. This research study analysed 53 pesticides and degradation products to evaluate their presence in drinking water. The most frequently detected pesticides in drinking water were atrazine, metolachlor, imidacloprid, hydroxyatrazine, imazethapyr and 2.4D. During the sample collection period, 25% of the soil was planted with winter crops, while just under 50% was allocated to summer crops, especially corn and soybeans. The correlation between the pesticides used in these crops and those found in drinking water was significant/notable. As a matter of fact, the individual concentration of pesticides in drinking water [25] exceeded the European limit in 8.7% and 17.6% of the samples collected from public and private water supplies, respectively, while the cumulative concentration of pesticides in drinking water exceeded the limit in 4.3% and 13.9% of the samples from public and private supplies, respectively. Based on these findings, we recommend/propose the inclusion of pesticides within the regulatory framework that governs the quality control of drinking water to guarantee the protection of public health and progressively reduce the use of pesticides in the Argentine agricultural system. Adopting these measures will contribute to ensuring the safety and sustainability of drinking water sources for the population.